Strategic valorization of invasive alien plants: A bioeconomic review for sustainable product development - Patil, Pragati; Divya, M. P.; Parthiban, K. T.; Balasubramanian, A.; Varadha Raj, S.; Ravi, R.; Ashick Rajah, R. (Frontiers in Plant Science, 2026)
Invasive alien plant species (IAPS) pose serious ecological and economic threats due to their aggressive proliferation and disruption of native ecosystems. However, their high biomass yield and rich phytochemical profiles offer significant potential for value-added utilization within circular bioeconomy frameworks. This review evaluates five major IAPS viz., Lantana camara, Prosopis juliflora, Leucaena leucocephala, Acacia mearnsii, and Senna spectabilis for their suitability in bioenergy, pulp and paper, natural dye production, pharmaceuticals, compost, and engineered wood. Quantitative assessments using multi-criteria scoring, pharmacological activity heatmap, and biomass-to-product flow models reveal that P. juliflora is the most versatile species, showing high performance across all categories, while L. camara and L. leucocephala emerge as specialized candidates for dyes, pharmaceuticals, and fodder applications, respectively. S. spectabilis exhibits biochar and soil improvement potential, and A. mearnsii demonstrates value in pulp and water purification. Despite technical and regulatory challenges, the strategic valorization of IAPS can simultaneously advance ecological restoration and green economic development. The article emphasizes integrative approaches and policy support for mainstreaming IAPS-based resource management.